Pengaruh Motivasi Terhadap Kecenderungan Kecurangan Akuntansi (Studi Empiris pada OPD Kota Solok) - Sari, Novita; Maison, Witra; Wahyuni, Lili (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The study aims to find out how much motivation influences the tendency of accounting fraud in the Solok City Regional Apparatus Organization. The research sample of 72 respondents consisted of the Head, Head of Finance, and treasurer in each OPD in Solok City.   Data collection used a questionnaire with a Likert scale.  Data analysis was carried out using simple linear regression analysis. The results of data analysis showed that overall, there was no significant influence of motivation on the tendency of accounting fraud in the Solok City regional apparatus organization